TEACHERS AND STUDENTS’ PERCEPTION OF AI IN ACCOUNTING EDUCATION: A CASE STUDY - Ahadi, Ahadi; Jatmika, Surya (Universitas Islam Sumatera Utara (UISU), 2025)
This study explores the perception of teachers and students at SMKN 1 Boyolali regarding the integration of Artificial Intelligence (AI) in accounting education. Using a qualitative case study approach, data were collected from three accounting teachers and three students through interviews and observations. The findings show that AI improves data analysis, personalizes learning, and provides instant feedback, aiding students in understanding complex accounting concepts. In addition, AI also contributes to the efficiency of administrative task management and the provision of more interactive teaching materials. However, obstacles such as limited infrastructure, inadequate internet connectivity, and lack of training for teachers and students hinder the optimal use of AI in the learning process. The study underscores the need for improved technology infrastructure, more comprehensive teacher training, and supporting policies that can encourage the effective use of AI in vocational accounting education. Thus, the results of this research are expected to provide insight for stakeholders in designing AI-based learning strategies that are more innovative and relevant to the latest technological developments.